Penerapan Senam Dismenorea pada Siswi SMP Negeri 11 Kota Jambi - Pebrianti, Dwi Kartika; Yanti, Rahmi Dwi; Putri, Vevi Suryenti; Yuliana, Yuliana; Rahmadhani, Dwi Yunita; Yesni, Marnila; Armina, Armina (Universitas Baiturrahim, 2025)
Menstruation is the process of releasing healthy blood and tissue from the uterus which then flows out of the body through the vagina. Disturbance that usually occurs during menstruation is dysmenorrhea. As a result,it can interfere with daily activities such as school, impaired motivation and concentration in learning. The aim of education is so that young women, especially female students at SMP N 11 Jambi City can do dysmenorrhea exercises to prevent dysmenorrhea pain. The activity begins with a pretest, then the implementation of education and demonstrations regarding dysmenorrhea and then a posttest. The media used are posters, ppt, leaflets and questionnaires. The educational target is 20 respondents. This activity was carried out at SMP Negeri 11 Jambi City for a period of 3-6 months in March 2023-July 2023. The results obtained were that before being given knowledge about the application of dysmenorrhea gymnastics from 20 participants 13 students said moderate pain with a pain scale range of 4-6 and after given knowledge about theapplicationofdysmenorrhoeagymnastics,therewere15participantswhosaidmildpainwithapainscale range of 1-3.It is hoped that this can provide information to students of SMP Negeri 11 Jambi City regarding dysmenorrhea exercises, especially for students who have experienced dysmenorrhea but have never been educated about how to deal with dysmenorrhea with dysmenorrhea exercises.